Tenth Anniversary of eHealth at the National Institute of Public Health - Rant, Živa; Štupica, Eva; Janet, Jure; Knavs, Miha; Tepej Jočić, Lucija; Malešič, Matjaž; Hafner, Eva; Simeunović, Boško; Čančarević, Dijana; Indihar, Simon; Kosednar, Hajdi (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
In 2015, the National Institute of Public Health of the Republic of Slovenia (NIJZ) assumed responsibility for managing the solutions of eHealth project. Since then, eHealth services have been continuously upgraded and improved. The use has steadily expanded, as has the range of content and functions available to patients and healthcare professionals. Despite the challenges NIJZ faced in introducing innovative solutions at the national level, the services have been successfully implemented. Today, eHealth services play a crucial role in supporting healthcare providers and facilitating electronic access to health records for the entire population. The most significant achievement of the Slovenian eHealth is its full population coverage, making it one of the few such examples worldwide. This paper describes the main characteristics and achievements of the eHealth solutions, including ePrescription, the zVEM patient portal, the zVEM+ healthcare professionals portal, eAppointment, the Central Registry of Patient Data, the eHeath Users Database, Teleradiology and TeleStroke. It also presents data on how these services are used.